Strategi Pengembangan SDM Polisi Siber (Cyber Police) di Satuan Kewilayahan Dalam Rangka Mewujudkan Polri 4.0.: Strategi Pengembangan SDM Polisi Siber (Cyber Police) di Satuan Kewilayahan Dalam Rangka Mewujudkan Polri 4.0. - Tjahyono, Frans; Nurhasim, Moch; Bintang, Bintang; Irawan, Dhanny (Pusat Penelitian dan Pengembangan Polri, 2025)
Current advances in information technology have helped humans carry out various activities and influenced people's lives globally. However, some parties use information technology to commit crimes known as cyber crimes. This increasingly diverse cyber crime requires the National Police to quickly adapt to this condition. This research was conducted to get a general picture of the condition of cyber police in regional units and the development of cyber police human resources in realizing police 4.0. The research was carried out using a mixed method research approach quantitatively and qualitatively with data collection techniques through distributing questionnaires to all personnel at the Sub-Directorate for Cyber ​​Crime and Criminal Investigation of the Regional Police and all personnel at the Tipiter Satreskrim Polres unit in the 11 sample Regional Police. Focus Group Discussions were carried out through interviews with informants at the Polda level such as Karo HR Polda, Dirreskrimsus Polda, Dirreskrimsus Polda, Kasubdit Cyber, Head of Cyber ​​Unit, Cyber ​​Investigators, while at the Polres level these were Kapolres/Waka, Head of HR, Kasatreskrim, Kasatreskrim, Kasatresnarkoba, Kanittipiter, Tipiter Investigator as well as a review of supporting documents. From the research, it is clear that there are still several obstacles that influence this. The lack of personnel and the uneven quality of Polri's human resources in the cyber sector are influencing factors in handling cyber crimes. Limited supporting equipment as well as adequate internet networks and software are also problems encountered. Apart from that, there are still fundamental obstacles such as the lack of budget support and the urgency of establishing a cyber police organizational structure in all regional units, considering the potential for cyber crime to threaten various levels of society in the midst of globalization.